PENGARUH PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR TEKNOLOGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - Fenny Rahmadhina Putri (Jurnal Riset Multidisiplin Edukasi, 2025)
This research aims to determine the effect of profitability, liquidity, and leverage on stock prices in the technology sector. This study uses secondary data from technology sector companies listed on the Indonesia Stock Exchange during the period of 2020-2023. The research employs purposive sampling technique. The data is tested using research data analysis methods, including descriptive analysis, multiple linear regression analysis, classic assumption tests, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The results of this study show that the t-test for the profitability variable (X1) has a calculated t value > t table (-7.121 > 1.66660) with a significance level (0.000 < 0.05), hence Ho is rejected and Ha is accepted. This means that the profitability variable has a negative but significant effect on the stock price variable. The t-test for the liquidity variable (X2) has a calculated t value < t table (-1.110 < 1.66660) with a significance level (0.271 > 0.05), thus Ho is accepted and Ha is rejected. This means that the liquidity variable does not have a significant effect on the stock price variable. The t-test for the leverage variable (X3) has a calculated t value < t table (1.592 < 1.66660) with a significance level (0.116 > 0.05), hence Ho is accepted and Ha is rejected. This means that the leverage variable does not have a significant effect on the stock price variable. Meanwhile, for the F test, it is known that fhitung > ftabel (18.477 > 2.49) with a significance level (0.000 < 0.05), therefore Ha is accepted and Ho is rejected, which means the independent variables, namely Profitability (X1), Liquidity (X2), and Leverage (X3) have a simultaneous effect on the dependent variable, which is Stock Price (Y). Meanwhile, the correlation analysis (R) of 0.660 indicates a strong correlation between Profitability (X1), Liquidity (X2), and Leverage (X3) towards Stock Price (Y) in the technology sector listed on the Indonesia Stock Exchange for the period 2020-2023. The coefficient of determination analysis (R2) yields R2 = 0.435 (43.5%). This reveals that the influence of Profitability (X1), Liquidity (X2), and Leverage (X3) affects Stock Price (Y) by 43.5%. The remaining 56.5% is influenced by other variables not included in this study.